Lipoprotein Z, a hepatotoxic lipoprotein, predicts outcome in alcohol‐associated hepatitis. Issue 4 (7th December 2021) - Hu, Kunpeng; Perez‐Matos, Maria C.; Argemi, Josepmaria; Vilar‐Gomez, Eduardo; Shalaurova, Irina; Bullitt, Esther; Landeen, Lee; Sugahara, Go; Deng, Huiyan; Mathur, Karan; Tran, Stephanie; Cai, Huimei; et al.
Abstract: Background and Aims: Lipoprotein Z (LP‐Z) is an abnormal free cholesterol (FC)–enriched LDL‐like particle discovered from patients with cholestatic liver disease. This study aims to define the diagnostic value of LP‐Z in alcohol‐associated hepatitis (AH) and interrogate the biology behind its formation. Approach and Results: We measured serum levels of LP‐Z using nuclear magnetic resonance spectroscopy, a well‐established clinical assay. Serum levels of LP‐Z were significantly elevated in four AH cohorts compared with control groups, including heavy drinkers and patients with cirrhosis. We defined a Z‐index, calculated by the ratio of LP‐Z to total apolipoprotein B–containing lipoproteins, representing the degree of deviation from normal VLDL metabolism. A high Z‐index was associated with 90‐day mortality independent from the Model for End‐Stage Liver Disease (MELD) and provided added prognosticative value. Both a Z‐index ≤ 0.6 and a decline of Z‐index by ≥0.1 in 2 weeks predicted 90‐day survival. RNA‐sequencing analyses of liver tissues demonstrated an inverse association in the expression of enzymes responsible for the extrahepatic conversion of VLDL to LDL and AH disease severity, which was further confirmed by the measurement of serum enzyme activity. To evaluate whether the FC in LP‐Z could contribute to the pathogenesis of AH, we found significantly altered FC levels in liver explant of patients with AH. Furthermore, FC in reconstituted LP‐Z particles caused direct toxicity to human hepatocytes in a concentration‐dependent manner, supporting a pathogenic role of FC in LP‐Z. Conclusions: Impaired lipoprotein metabolism in AH leads to the accumulation of LP‐Z in the circulation, which is hepatotoxic from excessive FC. A Z‐index ≤ 0.6 predicts 90‐day survival independent from conventional biomarkers for disease prognostication.